Phosphonopyruvic acid: A probable precursor of phosphonic acids in cell-free preparations of Tetrahymena - Horiguchi, M.; Rosenberg, H. (Biochimica et biophysica acta. General subjects, 1975)
1. 1. In cell-free preparations of Tetrahymena, doubly labelled [ 32P]phosphoenol-[3- 14C] pyruvate gives rise to 2-aminoethylphosphonate and 2-amino-3-phosphonopropionate, labelled with the two isotopes in the same ratio as the starting compound. The result is consistent with an intra-molecular rearrangement of phosphoenolpyruvate in the biosynthetic sequence of carbon-phosphorus bond formation. 2. 2. Incubation of [ 32P] phosphoenolpyruvate with the same preparation, followed by treatment with 2,4-dinitrophenylhydrazine, yielded labelled hydrazones. When these were subjected to hydrogenolysis, the radioactivity was recovered in 2-aminoethylphosphonate and 2-amino-3-phosphonopropionate, suggesting that 2-phosphonoacetaldehyde and 3-phosphonopyruvic acid were probable precursors of the aminoalkylphosphonic acids. 3. 3. Radioactivity from 2-amino-3-phosphono-[3- 14C] propionic acid was incorporated into 2-aminoethylphosphonic acid, but incorporation of the radioactivity into lipids was negligible.